Comparative Assessment of Dental Status Indicators Changes During Pregnancy - Bilinskyi О. Я.; Bilinska В. Ю.; Hanhur І. Ю.; Izai М. Е.; Stoyka В. В. (Actual Dentistry, 2025)
Actuality. Because the condition of the oral cavity of pregnant women significantly impacts their health and the course of pregnancy, recently, increasing attention has been paid to oral hygiene, caries, and periodontal diseases during pregnancy. Assessing the risk of such pathologies will make it possible to prevent them promptly. Aim. To conduct a comparative analysis of changes in the parameters of dental status, the state of oral hygiene, and the state of periodontal tissues during pregnancy. Materials and methods: 86 patients were included in the study. The age of the research participants is from 18 to 35 years old. The intensity of caries was determined using the DMF index, the OHI-S index determined the level of oral hygiene, and the PMA index determined the state of the periodontal tissues according to generally accepted recommendations. Surveys on food and hygiene habits were conducted using a modified questionnaire. Systematization of numerical data was carried out in Microsoft Excel 2019 software (Microsoft Office 2019, Microsoft) Results. The prevalence of dental caries among pregnant women was 97.67 %, and according to the DMF index, the intensity was 9.67 ± 0.56. At the initial examination, 26.7 % of pregnant women had healthy periodontium, and 73.3 % had signs of gum inflammation. At the re-examination, 18.6 % had healthy gums without signs of inflammation, and 81.4 % had signs of inflammation of various degrees, which indicates the deterioration of the periodontal condition with the course of pregnancy. Orthodontic disorders were observed in 3.49 % of pregnant women. Conclusions. Preventing and treating periodontal tissues, as well as conducting sanitary and educational work among pregnant women, will help improve hygiene in the condition of the hard and soft tissues of the oral cavity during pregnancy. The obtained results indicate that pregnant women are insufficiently aware of hygiene tools and methods, type of nutrition, and methods of periodontal disease prevention.